2009
DOI: 10.1007/s00540-008-0728-x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of fentanyl reduces predicted effect-site concentration of propofol for flexible laryngeal mask airway insertion

Abstract: The propofol EC(50) for FLMA insertion was decreased by supplemental 0.25 microg x kg(-1) fentanyl without BIS, hemodynamic, or respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In the operating room, intravenous access was secured and routine monitoring was established using ECG, non-invasive blood pressure and oxygen saturation (Dräger Infinity Delta; Dräger Medical AG&Co.KGoA, Lübeck, Germany). After preoxygenation with 100% oxygen for 3 min, anaesthesia was induced with intravenous fentanyl 1 lg.kg )1 and 1% propofol 3-5 mg.kg )1 [12,13]. On loss of verbal contact and eyelash reflex [14], the anaesthetist checked if ventilation via facemask was possible, and then inserted the first airway device according to the manufacturers' instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In the operating room, intravenous access was secured and routine monitoring was established using ECG, non-invasive blood pressure and oxygen saturation (Dräger Infinity Delta; Dräger Medical AG&Co.KGoA, Lübeck, Germany). After preoxygenation with 100% oxygen for 3 min, anaesthesia was induced with intravenous fentanyl 1 lg.kg )1 and 1% propofol 3-5 mg.kg )1 [12,13]. On loss of verbal contact and eyelash reflex [14], the anaesthetist checked if ventilation via facemask was possible, and then inserted the first airway device according to the manufacturers' instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the CP 50 s in the Supreme TM , ProSeal TM , I-gel TM and Laryngeal Tube Suction II TM groups were 5.8, 4.9, 5.7 and 5.5 µg/ml, respectively. Previous studies reported that the use of low dose fentanyl combined with propofol could markedly reduce the blood concentration of propofol necessary to suppress body movement during LMA insertion 15,16 . Therefore, we used intravenous fentanyl 2 µg/kg for 5 minutes before…”
Section: Discussionmentioning
confidence: 99%
“…Similar study was done by Yumura et al . [ 15 ] suggested that EC 50 of propofol for LMA insertion was decreased by supplementing 0.25 μg/kg fentanyl without haemodynamic or respiratory depression.…”
Section: Discussionmentioning
confidence: 99%